Implementation of Leadership Commitment to Employee Performance Quality Using the Six Building Blocks Method - Agustina, Cynthia; Indriyani, Yeni; Nurhadiyastuti, Ameilia; Setyawan, Agus (Newinera Publisher, 2025)
Hospital leadership commitment plays a crucial role in planning environmental health initiatives by allocating the necessary resources. Although the achievement of Minimum Service Standards at Ir. Soekarno Regional General Hospital is considered outstanding, challenges remain, such as expired training certifications, unmet opportunities for training renewal, and procedural non-compliance by some staff members. Therefore, leadership must enhance employee career development to foster organizational commitment and improve the quality of service delivery. This study aims to analyze leadership commitment in improving employee performance at Ir. Soekarno Regional General Hospital using the six building blocks method. The research design is qualitative, utilizing semi-structured interviews with both leadership and employees. Informant sampling was conducted through purposive sampling, with data verification carried out using source and technique triangulation. The findings reveal that the leadership has established organizational commitment through policy support, optimization of information systems, training budgets, and active employee participation in decision-making. However, the application of the six building blocks method in the context of employee performance based on leadership commitment remains suboptimal, particularly in the health workforce component. While physical health support for employees is adequately addressed, mental health support in the workplace is still lacking. Therefore, more intensive dissemination of policies and mental health programs is necessary, particularly for staff in underrepresented units.